2018
DOI: 10.1016/j.bios.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Wirelessly powered and remotely controlled valve-array for highly multiplexed analytical assay automation on a centrifugal microfluidic platform

Abstract: In this paper we present a wirelessly powered array of 128 centrifugo-pneumatic valves that can be thermally actuated on demand during spinning. The valves can either be triggered by a predefined protocol, wireless signal transmission via Bluetooth, or in response to a sensor monitoring a parameter like the temperature, or homogeneity of the dispersion. Upon activation of a resistive heater, a low-melting membrane (Parafilm™) is removed to vent an entrapped gas pocket, thus letting the incoming liquid wet an i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 65 publications
0
36
0
Order By: Relevance
“…In (Torres Delgado et al, 2016), we demonstrated continuous on-disc readout of a chemiluminescent signal by fitting a silicon photo-multiplier (ASD-NUV1S-P from AdvanSiD) and the necessary amplification stage circuitry (a logarithmic amplifier, LOG112 from Texas Instruments) onto an ApplicationDisc, showing an accuracy higher than 96% when compared to a commercial benchtop luminometer (GloMax luminometer from Promega Corporation). In (Torres Delgado et al, 2018) we demonstrated how to integrate and automate up to 128 thermally actuated valves on-disc. These were individually activated by executing a predefined timed sequence, or triggered, based on mixing and separation states, the variables being monitored in our case.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In (Torres Delgado et al, 2016), we demonstrated continuous on-disc readout of a chemiluminescent signal by fitting a silicon photo-multiplier (ASD-NUV1S-P from AdvanSiD) and the necessary amplification stage circuitry (a logarithmic amplifier, LOG112 from Texas Instruments) onto an ApplicationDisc, showing an accuracy higher than 96% when compared to a commercial benchtop luminometer (GloMax luminometer from Promega Corporation). In (Torres Delgado et al, 2018) we demonstrated how to integrate and automate up to 128 thermally actuated valves on-disc. These were individually activated by executing a predefined timed sequence, or triggered, based on mixing and separation states, the variables being monitored in our case.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…For example, depending on the actual status of a particular variable state (eg. mixing, incubation, or sedimentation), a particular action may need to be initiated based on the analyst's opinion (Torres Delgado et al, 2018). Hence it is desirable to facilitate wireless and real-time interaction with the platform and the ongoing experiment, via the implementation of a bidirectional link.…”
Section: Module Iv: Low Energy Bluetoothmentioning
confidence: 99%
See 2 more Smart Citations
“…These lab-on-a-disc systems make specific use of the interplay of the frequency controlled centrifugal force and capillary action in a surface-functionalized network of micro-channels and cavities. Key liquid handling operations such as valving [44][45][46][47][48], metering [49,50], mixing [51,52], pumping [53][54][55], and switching/routing of flow [56,57] have been demonstrated.A major challenge for microfluidic systems is rapid mixing. In general, one can categorize micromixers according to different characteristics [58,59], e.g., batch and continuous flow mode, laminar and turbulent, planar and 3-dimensional geometry, low-or high-aspect-ratio structures, manufacturing technologies or active/passive mixers.…”
mentioning
confidence: 99%